1997
DOI: 10.1001/archneur.1997.00550160091022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Xanomeline, a Selective Muscarinic Receptor Agonist, on Cognitive Function and Behavioral Symptoms in Alzheimer Disease

Abstract: The observed improvements in ADAS-Cog and CIBIC+ following treatment with xanomeline provide the first evidence, from a large-scale, placebo-controlled clinical trial, that a direct-acting muscarinic receptor agonist can improve cognitive function in patients with AD. Furthermore, the dramatic and favorable effects on disturbing behaviors in AD suggest a novel approach for treatment of noncognitive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
455
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 574 publications
(491 citation statements)
references
References 47 publications
16
455
0
1
Order By: Relevance
“…Employing the CGI definition of responders (CGIp3) the patients treated with xanomeline did significantly better than the placebo treated group. Interestingly, even though gastrointestinal side effects were observed, they occurred to a considerably lesser extent than in the Alzheimer patient study (Bodick et al, 1997).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Employing the CGI definition of responders (CGIp3) the patients treated with xanomeline did significantly better than the placebo treated group. Interestingly, even though gastrointestinal side effects were observed, they occurred to a considerably lesser extent than in the Alzheimer patient study (Bodick et al, 1997).…”
Section: Discussionmentioning
confidence: 61%
“…However, potent parasympatomimetic side effects confound the clinical use of nonselective cholinergic receptor agonists. More recently, it has been reported that acetylcholinesterase inhibitors as well as the muscarinic M 1 /M 4 preferring receptor agonist xanomeline reduce psychoticlike symptoms in patients with Alzheimer's disease (Bodick et al, 1997;Cummings, 2000;White and Cummings, 1996). Even though these newer compounds have considerably less parasympatomimetic side effects, nausea and vomiting have been reported in Alzheimer patients taking these drugs (Doody et al, 2001;Bodick et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In fact muscarinic agonists like xanomeline, BuTAC, and PTAC (which are relatively devoid of D 2 activity) have been shown to be very active in CAR (Bymaster et al, , 2002 and xanomeline has been shown to have antipsychotic and pro-cognitive efficacy in humans (Bodick et al, 1997). However in the case of NDMC, in the dose range tested, it did not effectively inhibit CAR at the 20-90-min time point where other M 1 agonists/partial agonists have inhibited CAR significantly after s.c. administration .…”
Section: Discussionmentioning
confidence: 99%
“…M 1 receptor agonists have been reported to improve working memory in animals (Aura et al 1997;McDonald et al 1998) and xanomeline, a M 1 receptor agonist with minimal M 2 receptor blockade Shannon et al 1994Shannon et al , 2000, has also improved cognition, and decreased hallucinatory and delusional symptoms in Alzheimer's disease (Bodick et al 1997;Bymaster et al 1997) and perhaps schizophrenia, whereas M 1 receptor antagonists may worsen working memory in patients with schizophrenia (McEvoy 1987;Spohn and Strauss 1989;King 1990) and in animals (Bymaster et al 1993;Aura et al 1997;Roldan et al 1997). The atypical APD-induced cortical ACh release would be expected to increase M 1 receptor stimulation by diminishing M 1 receptor antagonism where it exists.…”
Section: Discussionmentioning
confidence: 99%